Comparative analysis of Methicillin-Resistant Staphylococcus aureus (MRSA) and Borderline Oxacillin Resistant Staphylococcus aureus (BORSA) in community and food of animal origin. Issue 23 (5th December 2020) - Zehra, Asima; Gulzar, Maliha; Singh, Randhir; Kaur, Simranpreet; Gill, J P S
ABSTRACT: The aim of this study was to illustrate the relative pervasiveness of Borderline Oxacillin Resistant Staphylococcus aureus (BORSA) and Methicillin-Resistant Staphylococcus aureus (MRSA) in community and food of animal origin and their relationship with other genetic determinants. Staphylococcus aureus isolates were subjected to E-test using the antibiotics: oxacillin, ceftriaxone, cotrimoxazole, vancomycin, genotypic tests for the genes mecA, vanA, blaZ, pvl gene and SCCmec typing. The prevalence of S. aureus (MRSA) in the food of animal origin and community settings was 21% (1.8% MRSA) and 21.9% (7.4% MRSA), respectively. SCC mec type V was prevalent among the food of animal origin, while SCC mec type IVa among the community isolates. The likelihood of MRSA presence among community isolates was three times more than in isolates from chicken and milk samples. Likewise, the likelihood of detecting pvl positive MRSA ( pvl + MRSA) isolates was 4-fold higher in the community setting than in the food of animal origin. The mecA negative BORSA ( mecA − BORSA) was a frequently observed phenotype among S. aureus isolates. Also, co-detection of pvl and cotrimoxazol resistance was reported in this study although there was no noteworthy correlation of cotrimoxazol resistance with the type of sample. Isolates from milk and community settings exhibit higher minimum inhibitory concentration to vancomycin (Vancomycin MIC creep, 2–4 µg/mL). Significance: Current study provides the information on the statistical relationship between the genetic determinants of S. aureus with respect to sample type, and additionally the correlation that exists between the pvl and MRSA, pvl and cotrimoxazol resistance, vancomycin MIC and MRSA/Methicillin-Susceptible S. aureus (MSSA). Abstract : Current study provides the information on the statistical relationship between the genetic determinants of S. aureus with respect to sample type, and additionally the correlation that exists between the pvl and MRSA, pvl and cotrimoxazole resistance, vancomycin MIC and MRSA/Methicillin-Susceptible S. aureus (MSSA).